ORGANIZATIONAL CAPITAL IN ENTERPRISE ARCHITECTURE - Kirill G. Skripkin (Статистика и экономика, 2016)
The paper describes a new approach to the description of organizational capital in enterprise architecture. This approach is focused on internal consistency of organizational mechanisms and their fit to the requirements of technologies in use and key employees. The description rests on Henry Mintzberg organizational design theory. The value of this description is demonstrated for the case of influence of Ministry of Education and Science policy on the organizational capital of the Russian university.